New water-based nanocapsules of poly(diallyldimethylammonium tetrafluoroborate)/ionic liquid for CO2 capture. Issue 2 (February 2023) - Polesso, Bárbara B.; Duczinski, Rafael; Bernard, Franciele L.; Faria, Douglas J.; dos Santos, Leonardo M.; Einloft, Sandra
Abstract: Encapsulated ionic liquids as green solvents for CO2 capture are reported in this work. We present a novel combination of water-based poly(ionic liquid) and imidazolium-based ionic liquids (Emim[X]). Poly(diallyldimethylammonium tetrafluoroborate)/Emim[X] capsules were developed for the first time using Nano Spray Dryer B-90. Capsules were characterized by FTIR, SEM/EDX, TEM, TGA, DSC, CO2 sorption, and CO2 /N2 selectivity, CO2 sorption kinetic and recycling were also demonstrated. Comparing the capsules reported in this work, the combination of poly(diallyldimethylammonium tetrafluoroborate) and the ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate (P[DADMA]/BF4 ) showed great potential for CO2 capture and CO2 /N2 separation, providing higher results (53.4 mg CO2 /g; CO2 /N2 selectivity: 4.58).